2022
DOI: 10.3892/etm.2022.11657
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Bardet‑Biedl syndrome due to novel variants in the BBS10 gene in a fetus with multiple anomalies: A case report

Abstract: Bardet-Biedl syndrome (BBS) is an autosomal recessive disorder characterized by obesity, mental retardation, retinal dystrophy, hypogenitalism and renal and polydactyly malformations. The last two malformations may be observed antenatally and are highly variable, making the prenatal diagnosis of BBS challenging. The present study investigated the molecular etiology of BBS and validated a method for prenatal diagnosis. A Chinese couple who had conceived two fetuses with multiple malformations, including hyperec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this series, 11 fetuses were diagnosed prenatally from 2019 to 2022 years ( Li et al, 2019 ; Qiang et al, 2019 ; Li et al, 2020 ; Jing et al, 2021 ; Cai et al, 2022 ; Dong et al, 2022 ; Yan et al, 2022 ) except for one patient reported in 2004 ( Hou, 2004 ). All fetuses presented abnormal kidney images and/or bilateral enlarged hyperechogenic kidneys that implied renal cysts, and one presented hydrometrocolpos and postaxial polydactyly with vaginal atresia ( Hou, 2004 ).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…In this series, 11 fetuses were diagnosed prenatally from 2019 to 2022 years ( Li et al, 2019 ; Qiang et al, 2019 ; Li et al, 2020 ; Jing et al, 2021 ; Cai et al, 2022 ; Dong et al, 2022 ; Yan et al, 2022 ) except for one patient reported in 2004 ( Hou, 2004 ). All fetuses presented abnormal kidney images and/or bilateral enlarged hyperechogenic kidneys that implied renal cysts, and one presented hydrometrocolpos and postaxial polydactyly with vaginal atresia ( Hou, 2004 ).…”
Section: Resultsmentioning
confidence: 94%
“…Among 153 patients ( Supplementary Table S1 ), there were 87 males, 53 females, and 13 unknown (including fetuses) ( Li et al, 2019 ; Qiang et al, 2019 ; Li et al, 2020 ; Jing et al, 2021 ; Cai et al, 2022 ; Dong et al, 2022 ; Tang et al, 2022 ; Yan et al, 2022 ). Among 124 patients with diagnostic age (also excluding 10 fetuses), their age ranged from 1.2 to 44 years old with a mean of 16.70 ± 9.90 years old.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations